PkM Pendampingan Penggunaan Aplikasi Wad’atul Mal Berbasis Desktop untuk Meningkatkan Layanan Tabungan Santri di Pondok Pesantren Nurul Jadid Wilayah Zaid Bin Tsabit Paiton Probolinggo - Matlubul Khairi; Mochammad Fahrezy Abel Syaputra; Syaroful Karomah; Muhammad Fais; Moh. Syukron Wahyudi; Ahmad Faizal Amin; Mohammad Syahrul Hasaniauthor (BADAN PENERBIT STIEPARI PRESS, 2023)
Islamic boarding schools are vital for shaping students' character, knowledge, and religious skills. Financial management is crucial for their sustainability, yet Wadi’atul Mal relies on a conventional system, leading to transaction tracking issues and potential errors. The Assistance Activity aims to enhance Wadi’atul Mal services at Nurul Jadid Islamic Boarding School, Zaid Bin Tsabit. Successfully implemented, it involved needs analysis, activity design, system development, and training. The benefits include improved services through a computerized application and trained users, achieving a 95% user understanding. The system's feasibility index is 76.67%, indicating it's very feasible.